2019
DOI: 10.3389/fendo.2019.00282
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Retrospective Cohort Trial on 4,828 IVF Cycles Evaluating Different Low Prognosis Patients Following the POSEIDON Criteria

Abstract: Objective: To study the actual controlled ovarian stimulation (COS) management in women with suboptimal response, comparing clinical outcomes to the gonadotropins consume, considering potential role of luteinizing hormone (LH) addition to follicle-stimulating hormone (FSH). Design: Monocentric, observational, retrospective, real-world, clinical trial on fresh intra-cytoplasmic sperm injection (ICSI) cycles retrieving from 1 to 9 oocytes, performed at Humanitas Fertility Cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…Women with low prognosis after ART treatment can be stratified by using the POSEIDON criteria. Despite many studies have reported the CLBR among POSEIDON groups 19,22,23 , to our knowledge, the long term perinatal and obstetric outcome is still unexplored among women with low prognosis stratified by the POSEIDON criteria. From the demographic characteristics and obstetric history, the majority of participants were found to have regular menses with highest mean for POSEIDON1, with normal BMI or overweight.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Women with low prognosis after ART treatment can be stratified by using the POSEIDON criteria. Despite many studies have reported the CLBR among POSEIDON groups 19,22,23 , to our knowledge, the long term perinatal and obstetric outcome is still unexplored among women with low prognosis stratified by the POSEIDON criteria. From the demographic characteristics and obstetric history, the majority of participants were found to have regular menses with highest mean for POSEIDON1, with normal BMI or overweight.…”
Section: Discussionmentioning
confidence: 96%
“…This urges deep exploration and robust researches in the subject matter. It follows that, since POSEIDON criteria were introduced within the last decade, several publications have opted to assess different fertility outcomes among the four groups of low prognosis defined by the criteria 18,19 . With the majority assessing the cumulative probability of pregnancies 20,21 , a few assessed cumulative probabilities of pregnancy.…”
mentioning
confidence: 99%
“…The COS protocol was chosen based on patients' characteristics and gynecologists' judgment, according mainly to Poseidon criteria (16)(17)(18).…”
Section: Methodsmentioning
confidence: 99%
“…More recently, a new classification of poor ovarian reserve patients in IVF/ART has been put forward by the POSEIDON (Patient Oriented Strategies Encompassing Individualized Oocyte Number) group (20)(21)(22). In this classification, four subgroups have been suggested according to qualitative and quantitative parameters, like the Bologna criteria, namely:…”
Section: Definition and Etiologymentioning
confidence: 99%